Post-fire germination and plant invasion in Mediterranean Chile - Ocampo-Zuleta, Korina; Paula, Susana; Pausas, Juli G.; Cavieres, Lohengrin A.; Sierra-Almeida, Angela; Gomez-Gonzalez, Susana (My University, 2025)
PremisePlants from regions where fire is a novel disturbance typically lack fire-adaptive traits, which may explain the post-fire invasion by alien plants from fire-prone ecosystems. Unlike many Mediterranean-type ecosystems, the Chilean matorral has a limited evolutionary history with fire. We predict that a negative germination response to fire will be more frequent in its native flora than in alien plants, most of which originate from the fire-prone Mediterranean Basin.MethodsWe compiled a database on the germination responses to fire cues of 70 native and alien plant species from the Chilean matorral using published studies and unpublished data from our own experiments. We then compared the frequency of these responses between native and alien species using generalized linear mixed models.ResultsNegative responses to heat shock were more probable in native than in alien species, while there were no differences in the probability of negative responses to smoke. Species origin did not affect the probability of positive responses to fire cues. When only annual plants were considered, natives and aliens did not differ in their germination responses to fire cues.ConclusionsOur findings suggest that the influence of post-fire germination on invasion processes in the Chilean matorral is better explained by the negative effects of heat on the germination of native species (which lack fire-adaptive traits) than by the positive response of alien species to fire cues. The reduced germination of natives creates opportunities for alien species establishment, rather than pre-existing fire adaptive traits driving invasion success.
Keywords: alien species; fire cues; heat shock; mediterranean-type ecosystems; seed germination; smoke